S98 A Novel Human Model To Study Alveolar Injury And Repair. (10th November 2014) - Alçada, J; Ng-Blichfeldt, JP; Proudfoot, AG; Griffiths, MJD; Dean, CH; Hind, M
Abstract : Introduction: The development of regenerative therapies holds promise for the future treatment of parenchymal lung diseases. However, encouraging preclinical data from animal models have translated poorly in clinical trials. The cellular and molecular response to lung injury is difficult to study in man. To address this fundamental question, we have developed a novel in vitro human model. Precision cut lung slice (PCLS) culture is a well-established tool in airway biology and pharmacology. Here, we demonstrate lung parenchyma can be maintained and manipulated in vitro generating a tractable model, which allows study of lung injury and repair in man. Methods: PCLS (500 µm) were generated from agarose-inflated lung lobes from human lungs maintained ex-vivo by perfusion and ventilation (EVLP). The slices were cultured in serum-free medium in a rotating incubator (37ºC, 5% CO2 ) and analysed at days 1, 3 and 7. Cell specific immunofluorescence markers were used to identify smooth muscle, type I and type II alveolar epithelial cells (AT1, AT2), vascular endothelial cells and proliferating cells (using αSMA, Aquaporin5, ProSPC, PECAM1 and Phospho-histone H3 respectively). Slice viability was confirmed using MitoTracker, LDH and Live/Dead assays. Results: All of the expected cell types were identified in PCLS by immunofluorescence demonstrating that human PCLS maintained cellular differentiation in culture. Pro-SPC was predominant in the alveolar wall cells, particularly in the alveolar septal junctions, corresponding to known location of AT2 cells; AQ5 was distributed in thin bands lining the alveolar walls suggestive of the apical membrane of AT1 cells; αSMA was positive around airways, the known location of smooth muscle cells (SMCs); PECAM-1 was positive within alveolar walls corresponding to microvascular capillaries within alveolar septae. There was no significant cell proliferation during culture under basal conditions. Finally, cell viability studies demonstrated that PCLS can be maintained for up to 1 week in serum-free culture. Conclusion: PCLS of human lung parenchyma remain differentiated and viable for up to 7 days in serum-free culture. In future, human PCLS derived from normal and injured regions of lung from the EVLP model may provide a novel means of studying alveolar repair in human lung in vitro .